Wakaf Tunai Menurut Pandangan Fiqh Syāfi‘iyah dan Fatwa Majelis Ulama Indonesia No 2 Tahun 2002 tentang Wakaf Uang - Mustafa Kamal (Tadabbur: Jurnal Peradaban Islam, 2019)
This study discusses cash waqf according to Syāfi'iyah and the Fatwa of the Indonesian Ulema Council (MUI). This research uses descriptive qualitative research method with comparative analysis method, while the approach in this research is content analysis approach. The steps taken in the research include data collection and data analysis taken from the source books (Fiqh Syāfi'iyah books and Naskhah Fatwa MUI). After the data is collected, it is then processed using the content analysis method. The purpose of this research is to describe all the diversity and uniqueness of the thoughts of fuqahā and Muslim figures. The research on cash waqf is focused on three things, namely: the definition of waqf, the law of cash waqf and its rationale in issuing a cash waqf ruling, and the understanding of the cash waqf argument. Research on the definition of waqf found differences in terms of the development of the scope of the study. According to MUI, it is necessary to add a sentence (baqā 'ashlih) from the basic formulation of the definition of waqf according to Shāfi'iyah, this is because the basis of the hadith of Ibn Umar about waqf which reads "ihbas ashlahā wa sabbil tsamaratahā". The Shāfi'iyah's definition of waqf is based on the limitation of waqf to fixed objects ('ain must be intact), which limits the permissibility of waqf to fixed objects only, excluding cash. The Shāfi'iyah base this on the principle of waqf property that must be eternal in its substance (baqā' 'ainih), not in the nature of the waqf item (nature or baqā' 'ashlih). From this study, it is also found that MUI's fatwa stipulates that cash waqf is permissible (jawaz) or valid, while Shāfi'iyah argues that it is not permissible (invalid).